Characteristics and indices of reproduction in Dorper sheep - Elias, P.; Cohen, D.; Dayenoff, Patricio Mario (South African Veterinary Association, 2020)
In seventeen adult Dorper ewes imported from South Africa into Israel and nine of their primiparous, first-generation daughters born in Israel, characteristics and indices of reproduction were determined during the period of April 1982 to April 1984. This study showed that, during the period from April 1982 to January 1984, three lambings occurred in the adult ewes; the lengths of the oestrous cycles for adult and primiparous ewes were 17.6 +/- 1.1 and 16.6 +/- 1.2 days, respectively; the number of services per ewe in oestrus were 3 +/- 1 services; the average length of pregnancy was 146-147 days; the lambing intervals were 6.2 +/- 0.46 and 7.7 +/- 0.62 months from the first to second lambing and the second to third lambing, respectively; of 17 ewes, 3 had twins in all 3 lambings (17.6%) and 4 had twins in only the first 2 lambings (23.5%). The sex ratio recorded in 70 lambs of adult ewes (in three lambings) was 41 males to 29 females (41:29). A high percentage of fecundity (137.2%) and prolificity (149%), an unrestricted breeding seasons, a short lambing interval and a short postweaning anoestrus period, recommend this breed of sheep as commercially advantageous for arid zones.